Neuronal SIRT1 regulates macronutrient-based diet selection through FGF21 and oxytocin signalling in mice. Issue 1 (December 2018) - Matsui, Sho; Sasaki, Tsutomu; Kohno, Daisuke; Yaku, Keisuke; Inutsuka, Ayumu; Yokota-Hashimoto, Hiromi; Kikuchi, Osamu; Suga, Takayoshi; Kobayashi, Masaki; Yamanaka, Akihiro; Harada, Akihiro; Nakagawa, Takashi; et al.
Abstract Diet affects health through ingested calories and macronutrients, and macronutrient balance affects health span. The mechanisms regulating macronutrient-based diet choices are poorly understood. Previous studies had shown that NAD-dependent deacetylase sirtuin-1 (SIRT1) in part influences the health-promoting effects of caloric restriction by boosting fat use in peripheral tissues. Here, we show that neuronal SIRT1 shifts diet choice from sucrose to fat in mice, matching the peripheral metabolic shift. SIRT1-mediated suppression of simple sugar preference requires oxytocin signalling, and SIRT1 in oxytocin neurons drives this effect. The hepatokine FGF21 acts as an endocrine signal to oxytocin neurons, promoting neuronal activation andOxt transcription and suppressing the simple sugar preference. SIRT1 promotes FGF21 signalling in oxytocin neurons and stimulatesOxt transcription through NRF2. Thus, neuronal SIRT1 contributes to the homeostatic regulation of macronutrient-based diet selection in mice. SIRT1 is a NAD+ -dependent deacetylase whose functions have been linked to organismal longevity, aging and metabolism. Here, Matsui and colleagues show that neuronal SIRT1 can affect nutrient-related dietary choice in mice, and this effect is mediated by FGF21 signalling and oxytocin.